Evaluation of Government Agency Websites under the 2017 KOMINFO Regulation Implementation of Government Agency Portals and Sites - Fahrianda, Olpis; Angraini, Angraini; Hamzah, M. Luthfi; Saputra, Eki (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The Public Works and Spatial Planning Office of Indragiri Hulu Regency (Dinas PUPR INHU) has the responsibility of formulating, stipulating, and implementing policies related to technical guidance and supervision of the implementation of affairs related to the Ministry of Public Works and Public Housing. The PUPR INHU Office also develops a website to improve the effectiveness of public services, provide relevant information, and publish documents related to the duties and functions of the PUPR Indragiri Hulu Office which are in the process of realization. However, the website tends to be poorly managed because there are still some features that cannot be controlled, the information provided is not realtime, and there have been errors or failures in accessing the site. The purpose of this research is to evaluate the INHU PUPR Office website based on the provisions contained in the Regulation of the Minister of Communication and Information of the Republic of Indonesia of 2017 concerning the Implementation of Government Agency Portals and Websites. The evaluation aims to provide guidelines for organizing Government portals and websites. Based on the results of testing conducted with 11 test criteria on the INHU PUPR Office website, the test results with an overall score weight of 73.8% indicate that the INHU PUPR Office website is of Quite Quality.